2006
DOI: 10.1096/fj.06-5865com
|View full text |Cite
|
Sign up to set email alerts
|

A pivotal role of matrix metalloproteinase‐3 activity in dopaminergic neuronal degeneration via microglial activation

Abstract: Recent studies have demonstrated that activated microglia play an important role in dopamine (DA) neuronal degeneration in Parkinson disease (PD) by generating NADPH-oxidase (NADPHO)-derived superoxide. However, the molecular mechanisms that underlie microglial activation in DA cell death are still disputed. We report here that matrix metalloproteinase-3 (MMP-3) was newly induced and activated in stressed DA cells, and the active form of MMP-3 (actMMP-3) was released into the medium. The released actMMP-3, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
146
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(155 citation statements)
references
References 29 publications
9
146
0
Order By: Relevance
“…MMP-3 released by dying neurons activates microglia, further contributing to neurodegeneration (Kim et al 2007) along with MMP-9 (Woo et al 2008). Altered gelatinase expression in the SN of post-mortem brains of PD patients was first reported by Lorenzl et al (2002), according to whom no alteration in MMP-9 protein and activity levels were observed compared to age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP-3 released by dying neurons activates microglia, further contributing to neurodegeneration (Kim et al 2007) along with MMP-9 (Woo et al 2008). Altered gelatinase expression in the SN of post-mortem brains of PD patients was first reported by Lorenzl et al (2002), according to whom no alteration in MMP-9 protein and activity levels were observed compared to age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 and -9 are highly expressed in the brain in physiological conditions, and MMP-9 and -3 are significantly up-regulated in several brain pathologies, including PD (Lorenzl et al 2002, Kim et al 2007Choi et al 2008), highlighting them as possible therapeutic targets (Leonardo and Pennypacker 2009). Specific MMP inhibitors have been developed; however, indiscriminate block of this enzymatic activity is a dangerous ground, since MMPs play different roles depending on the type of pathology and time of activation.…”
Section: Introductionmentioning
confidence: 99%
“…31 Moreover, activated MMP-3 is present in the nuclear compartment of malignant and nontransformed hepatocytes, and is associated with the onset of apoptosis. 32 These studies suggested a novel function of MMP-3 as a signaling molecule active for intracellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies provided molecular details to the understanding of the neuroinflammaotry component in PD. It has been shown that the products secreted by damaged neurons ( [251,121]) aggregated alpha-synuclein or environmental toxins such as LPS are recognised by the macrophage antigen complex 1, Mac-1, a PRR expressed on microglia cells; in turn, Mac-1 activation is crucial for activation of NADPH oxidase, a membrane-bound enzyme that catalyses the production of superoxide anions, which are released in the extracellular space, and generates intracellular ROS, well known triggers of the inflammatory response ( [18,122,223,264]). NADPH oxidase is associated with neurodegenerative disorders and neuronal damage; it is activated in the brains of patients with PD [252].…”
Section: Animal Models Of Parkinson's Diseasementioning
confidence: 99%